Why are the sugar cane harvesters dying? - Alves, Francisco (Saúde e Sociedade, 2006)
The objective of this paper was to demonstrate that deaths of sugar-cane cutters in Brazil are caused by the payment rules in this sector. The productive and labor processes now instituted in the Brazilian sugar-cane sector had the aim of increasing productivity of labor and the main form of payment is per production. This results in the increase of the worker's efforts during the labor process. The increase of energy and effort spent by the workers to cut sugar-cane has become too depreciating for the workers, and, in the limit, is causing the death of such workers or their early loss of labor capacity.